Sense of coherence and its relationship to participation, cancer-related fatigue, symptom burden, and quality of life in women with breast cancer participating in the OptiTrain exercise trial - Hiensch, Anouk E (Support Care Cancer, 2020)
PURPOSE: This study examined the Sense of Coherence (SOC) of patients participating in the randomized controlled ‘Optimal Training for Women with Breast Cancer’ (OptiTrain) study and assessed how patient characteristics were associated with SOC. Secondary aims were to assess the association between SOC and patients’ participation in this study and to determine whether SOC moderates the effect of the 16-week exercise intervention on fatigue, quality of life (QoL), and symptom burden in women with breast cancer undergoing chemotherapy. METHODS: Modified Poisson regression analyses were conducted to determine the relative risk of weak-normal SOC versus strong SOC in terms of exercise session attendance, study and intervention dropout, and long absence rates. Analyses of covariance were performed to assess whether SOC moderated the effect of the exercise intervention (p(interaction) ≤ 0.10). RESULTS: Two hundred and forty women with early breast cancer (mean age 53 ± 10) participated in the OptiTrain study. Women with strong SOC reported less fatigue, lower symptom burden, and higher QoL. Women with weak-normal SOC were significantly more likely to drop out from the OptiTrain study and tended to have slightly poorer exercise session attendance. Women with breast cancer and weaker SOC benefitted as much from the exercise intervention, in terms of fatigue and QoL, as those with stronger SOC (p(interaction) > 0.10). CONCLUSIONS: Strong SOC appears to be associated with a more positive subjective state of health. Women with weak-normal SOC may need additional support to encourage participation and adherence in exercise trials. Assessing SOC may assist clinicians to identify and provide extra support for participants with weak SOC, who may be less inclined to participate in exercise programs. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00520-020-05378-0) contains supplementary material, which is available to authorized users.